2010
DOI: 10.1074/jbc.m109.091207
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Mechanism of p130Cas Localization to Focal Adhesions

Abstract: The docking protein p130Cas is a major Src substrate involved in integrin signaling and mechanotransduction. Tyrosine phosphorylation of p130Cas in focal adhesions (FAs) has been linked to enhanced cell migration, invasion, proliferation, and survival. However, the mechanism of p130Cas targeting to FAs is uncertain, and dynamic aspects of its localization have not been explored. Using live cell microscopy, we show that fluorophore-tagged p130Cas is a component of FAs throughout the FA assembly and disassembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 58 publications
5
85
0
Order By: Relevance
“…For example, Src-mediated phosphorylation triggers paxillin-promoted disassembly (32,36,37), which allows release of the ECM as new FAs form at the leading edge (11). We found that PEAK1 enters FAs after both paxillin (supplemental Table S1) and ā£-actinin (data not shown) and persists in adhesions after paxillin (supplemental Movie 4) is gone, suggesting that PEAK1 functions more in the later stages of FA development and turnover than in FA initiation (11,38). These findings are consistent with PEAK1 increasing FA length (17) and promoting longer FA lifetimes (Figs.…”
Section: Discussionmentioning
confidence: 85%
“…For example, Src-mediated phosphorylation triggers paxillin-promoted disassembly (32,36,37), which allows release of the ECM as new FAs form at the leading edge (11). We found that PEAK1 enters FAs after both paxillin (supplemental Table S1) and ā£-actinin (data not shown) and persists in adhesions after paxillin (supplemental Movie 4) is gone, suggesting that PEAK1 functions more in the later stages of FA development and turnover than in FA initiation (11,38). These findings are consistent with PEAK1 increasing FA length (17) and promoting longer FA lifetimes (Figs.…”
Section: Discussionmentioning
confidence: 85%
“…9) where integrin activation induces Src-mediated phosphorylation of PTPā£ at Tyr789, resulting in formation and localization of a PTPā£-BCAR3-Cas complex at nascent adhesion sites. Since BCAR3 interacts with the C-terminal region of Cas, specifically with the helix-containing Cas family C-terminal homology do- main (CCH) region of Cas required for its optimal focal adhesion localization (13,17), we propose that this mechanism underlies the C-terminal-dependent focal adhesion localization of Cas. Consistent with this, BCAR3 has been suggested to regulate migration by promoting Cas localization to the membrane or leading edge (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, virtually nothing is known of BCAR3-SH2 specificity, and besides PTPā£, no other target phosphotyrosyl proteins have been found. Two domains of Cas mediate its targeting to adhesion complexes, and both domains are required for optimal focal adhesion recruitment and tyrosine phosphorylation of Cas (13,18,28). The N-terminal SH3 domain of Cas associates with FAK to recruit Cas to focal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Tight regulation of p130Cas function via proteolytic cleavage or reversible phosphorylation of tyrosine residues is necessary for the maintenance of cell motility, survival, and apoptosis in various cell types. [5][6][7][8] Although high expression of p130Cas in primary breast tumors is linked to activation of cell proliferation and cancer progression, the detailed mechanisms governing p130Cas expression are not fully understood.…”
mentioning
confidence: 99%